The Role of Logistics Management in Public Services – Research Plan - Buics, László (International Journal of Engineering and Management Sciences, 2017)
Public services and logistics are generally treated as different fields, but the tools of logistics management with the help of the Unified Services Theory can be used for the benefit of the public services. The aim of this theoretical paper is to generally introduce my topic and relevance of the research on which my PhD thesis will be based in the future. The expectations in the advanced, globalized world are pushing governments to find new methods to fulfil the needs of the citizens while keeping up or even increase efficiency and effectiveness. I believe that from a certain viewpoint the public administration system can be considered as a large scale supply network, and I am particularly interested in how we could apply logistical methods in public services to increase efficiency and effectiveness while simultaneously increase customer satisfaction. In this particular paper I would like to present how I see the connections between the concept of New Public management and the Unified Services Theory. I would like to show the similarities between them and how they could complete each other in order to serve as a background for later logistics related approaches and researches within the domain of public services.